Experimental and theoretical evaluation of the tensile properties of carbon nanotube-coated carbon fibre hybrid composites - Md. Aziz, Shazed (2013)
Hierarchically structured hybrid composites are ideal engineered materials to carry loads and stresses due to their unconventional in-plane specific mechanical properties such as tensile modulus, strength, and stiffness. Growing carbon nanotubes (CNT) on the surface of high performance carbon fibres (CF) provides a means to tailor the mechanical properties of the fibre-matrix interface of a composite. The growth of CNT onto the surface of CF was conducted via floating catalyst chemical vapor deposition (CVD) technique. The mechanical properties of the resultant fibres, CNT density and alignment morphology were shown to depend on the CNT growth temperature, growth time, carrier gas flow rate, catalyst amount, and atmospheric conditions within the CVD chamber. The evidence of intensive CNTcoating on CF was shown at a CVD temperature of 700 °C and 30 minutes reaction time by using Scanning electron microscope (SEM). Single fibre/Epoxy composite coupons were fabricated by using both neat and CNT-coated CF to conduct single fibre fragmentation test (SFFT). For neat-CF/Epoxy composite coupons, IFSS was found to be 12.52 MPa. A CNT-coated CF demonstrated approximately 45% increase in calculated IFSS when treated at 700 °C and 30 minutes reaction environment over that of the untreated fibre from which it was processed. Carbon nanotube coated short carbon fibre reinforced polypropylene (CNT-CF/PP) composites were fabricated. The resulting hybrid composite samples were characterized using the tensile testing method. For neat-CF/PP composite, Young’s modulus and tensile strength were found to be 1.72 GPa and 20.5 MPa respectively. In contrast with the neat CF/PP composite, CNT-CF/PP composite has shown enhanced Young’s modulus by approximately 104% and tensile strength increased to approximately 64%. The fibre-matrix adhesion was analyzed by using SEM on cryogenically fractured surface of both types of composites. The proper justification of fibre-matrix interfacial adhesion featuring the composite tensile properties was explained through interfacial shear strength (IFSS). Composites with high IFSS was found to show a high Young’s modulus and tensile strength. Theoretical prediction of hybrid CNT-CF/PP composite tensile properties was accomplished by using a hierarchical model which comprises Halpin–Tsai equations, Combined Voigt-Reuss model, simple rule-of-mixtures (RoM) and Krenchel approach. When the internal geometry of composite was a key factor RoM was utilized to study the fibre orientation distribution in the composite. A comprehensive fractographic investigation was carried out with scanning electron microscope (SEM) to analyze the fibre orientation distribution on the CNT-CF/PP composite fracture surfaces. Then, a thorough analysis was done on the SEM images using Bersoft and Geozebra image analyzing software packages to evaluate the fibre orientation distribution factor (η 0 ). In the context of this approach, when the fibre orientation effect is ignored a noteworthy deviation in tensile modulus with 51% was notified rather than experimental result of 1.72 GPa. When η0 is considered a more acceptable validation with the experimental results of tensile modulus was obtained which shows amoderate deviation with 30% to the predicted value of 4.57 GPa. Finally, the discrepancies between the predicted and experimental values were explained in terms of stress-strain behavior.